High CXCR3 expression in synovial mast cells associated with CXCL9 and CXCL10 expression in inflammatory synovial tissues of patients with rheumatoid arthritis - Ruschpler, Peter (BioMed Central, 2003)
To improve our knowledge on the pathophysiology of rheumatoid arthritis (RA), we investigated gene expression patterns in synovial tissue from RA and osteoarthritis (OA) patients. DNA oligonucleotide microarray analysis was employed to identify differentially expressed genes in synovial tissue from pathologically classified tissue samples from RA (n = 20) and OA patients (n = 10). From 7131 gene sets displayed on the microarray chip, 101 genes were found to be upregulated and 300 genes to be downregulated in RA as compared with OA. Semiquantitative reverse-transcription polymerase chain reaction, Western blotting and immunohistochemistry were used to validate microarray expression levels. These experiments revealed that Cys–X–Cys receptor (CXCR)1, CXCR2 and CXCR3 mRNAs, as well as Cys–X–Cys ligand (CXCL)9 (monokine induced by IFN-γ) and CXCL10 (IFN-γ inducible protein 10) mRNAs, were significantly upregulated in RA as compared with OA disease. Elevated protein levels in RA synovial tissue were detected for CXCR1 and CXCR3 by Western blotting. Using immunohistochemistry, CXCR3 protein was found to be preferentially expressed on mast cells within synovial tissue from RA patients. These findings suggest that substantial expression of CXCR3 protein on mast cells within synovial tissue from RA patients plays a significant role in the pathophysiology of RA, accompanied by elevated levels of the chemokines CXCL9 and CXCL10. Mature mast cells are likely to contribute to and sustain the inflamed state in arthritic lesions (e.g. by production of inflammatory mediators such as histamine, proteinases, arachidonic acid metabolites and cytokines). Thus, the mast cell could become a potential target in therapeutic intervention.